Stable isotope analysis of New Zealand sea lion (Phocarctos hookeri) whiskers shows distinct regional ecological niches - Chilvers BL; Galbraith D (Elsevier BV, Amsterdam, 2025)
A region's isoscape (isotopic values within a marine ecosystem) can vary markedly, providing the ability to assess the foraging and migration behaviours of apex marine predators through stable isotope analysis of inert tissue such as whiskers. Additionally, these values can be used to determine the area of origin. The New Zealand sea lion (Phocarctos hookeri) breeds over 7 degrees of latitude from Otago Peninsula (45.8°S), South Island, New Zealand, to Campbell Island (52.5°S), a 750 km distance. For most of their range, there is incomplete description of their foraging ecology and diet. We analysed δ13C and δ15N stable isotope ratios from pup whiskers (n = 160) from the five main breeding areas, across three distinct regions for New Zealand sea lions. We investigated isotopic niches for each breeding area to give insight into foraging behaviours and determined whether isotopic values could be used to identify the place of origin of individuals. We found significant differences in isotopic values between the five breeding areas except Enderby and Dundas Islands, Auckland Islands. The differences between breeding areas are likely driven by a combination of prey abundance, distribution and consumption by the pups' mothers, underlying oceanographic variability, varying isotopic baselines, and potential impacts from human influences. Isotopic niche widths were greatest in the Auckland Islands region. This research highlights the value of stable isotope analysis to investigate regional scale variations of apex marine predators foraging and could provide insight into anthropogenic and environmental factors that could influence resource use
Keywords: Diet; Foraging ecology; Isotopic niche width; Phocarctos hookeri; Pinniped